Analog and Numerical Experiments of Double Subduction Systems With Opposite Polarity in Adjacent Segments. (24th June 2020) - Peral, Mireia; Ruh, Jonas; Zlotnik, Sergio; Funiciello, Francesca; Fernàndez, Manel; Vergés, Jaume; Gerya, Taras
Abstract: In this work we study the dynamics of double subduction systems with opposite polarity in adjacent segments. A combined approach of numerical and analog experiments allows us to compare results and exploit the strengths of both methodologies. High‐resolution numerical experiments complement laboratory results by providing quantities difficult to measure in the laboratory such as stress state, flow patterns, and energy dissipation. Results show strong asymmetries in the mantle flow that produce in turn asymmetries in the trench and in the downgoing slab deformation. The mantle flow pattern varies with time; the toroidal cells between the plates evolve until merging into one unique cell when the trenches align. In that moment the maximum upward flow is observed close to the trenches. The interaction between the mantle flow produced by each subducting plate makes the rollback processes slower than in a single subduction case. This is consistent with the observed energy dissipation rate that is smaller in the double subduction system than in two single subductions. Moreover, we provide a detailed analysis on the setup and boundary conditions required to numerically reproduce the analog experiments. Boundary conditions at the bottom of the domain are crucial to reproduce their analog counterparts. Numerical results are compared to natural examples of multi‐slab subduction systems in terms of upper mantle seismic anisotropy, relative trench retreat velocities, and composition of subduction‐related magmatism. Key Points: Numerical models of double subduction have been developed to reproduce laboratory experiments and to understand the dynamics of the system The interaction between the induced mantle flows slows down the evolution of the system and generates additional deformation of plates In the horizontal plane mantle flow forms four toroidal cells with symmetry axes that rotate during trench retreat